Implementation of SWOT and Blue Ocean Strategy in Facing Competition for New Student Admission - Murtanti, Wilin; Satori , Djam'an; Suryadi; Chusnul Kurniatun , Taufani (BRILIANT: Jurnal Riset dan Konseptual, 2025)
This study is motivated by the public perception that the quality of private high schools in Rayon 12 DKI Jakarta is still low. The determining factor for the quality and effectiveness of teaching and learning in schools is competent teachers. Quality teachers have a direct effect on overall educational performance. The high and low competence of the teachers themselves can be determined by the leadership of the principal and school culture. The purpose of this study is to analyze the competitiveness of SMAS X to get excellent students. The research method used is qualitative with a case study approach. The data used are literature studies, questionnaires and observation results. The research results are as follows: 1). Principal leadership, school culture, teacher competence, are able to improve quality; 2). There is an increase in interest in the admission of new students (PPDB); 3). The application of Blue Ocean Strategy (BOS) in education will increase the strong competitiveness of the institution.